Automata, Languages and Programming 37th International Colloquium, ICALP 2010, Bordeaux, France, July 6-10, 2010, Proceedings, Part I - Abramsky, Samson.; Gavoille, Cyril.; Kirchner, Claude.; Meyer auf der Heide, Friedhelm.; Spirakis, Paul G. (Lecture Notes in Computer Science, 2010)
The two-volume set LNCS 6198 and LNCS 6199 constitutes the refereed proceedings of the 37th International Colloquium on Automata, Languages and Programming, ICALP 2010, held in Bordeaux, France, in July 2010. The 106 revised full papers (60 papers for track A, 30 for track B, and 16 for track C) presented together with 6 invited talks were carefully reviewed and selected from a total of 389 submissions. The papers are grouped in three major tracks on algorithms, complexity and games; on logic, semantics, automata, and theory of programming; as well as on foundations of networked computation: models, algorithms and information management. LNCS 6198 contains 60 contributions of track A selected from 222 submissions as well as 2 invited talks.